Hubungan Antara Penerapan Sistem Pembelajaran Moving Class Dengan Motivasi Dan Hasil Belajar Pada Mata Pelajaran Informatika - Zahra Nafilatul Husna; Albani Idris; Elfina Elfina; Siti Romla; Nurin Kartika Wahyuningsih; Miftahus Surur; Nur Azizah (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
Moving class learning is a learning system that is carried out by moving classes according to the schedule of subjects that will be followed by students where the teacher is already in the classroom and ready to start learning. This research aims to describe moving class learning with motivation and learning outcomes. The method used in this research is a literature review. Literature Review is a search and research of the literature by reading and reviewing various journals, books and various other published manuscripts related to the research topic to produce an article relating to a particular topic or issue. This research collects data from related articles published in the 2012-2024 period via Google Scholar. A total of 11 articles were selected and analyzed based on the research methods used.